Social support as a shield: preventing burnout in elite athletes through strong networks - Saeed, I.; Xigen, W.; Khan, I.; Dukhaykh, S.; Ahmad, A. (Journal of Sports Sciences, 2025)
This study aimed to investigate the impact of perceived social Support on burnout in elite athletes. Further, this study also examined the mediating role of strong social networks in this relationship. Based on a sample of 340 elite athletes in Wuhan, China, the study employed the Athletes` Received Support Questionnaire (ARSQ), the Athlete Burnout Questionnaire (ABQ), and the Social Connectedness Scale-Revised (SCS-R). The results indicated that (1) there was a significant negative relationship between perceived social support and athlete burnout; (2) social Support was directly positively correlated with athletes` strong social network; (3) the strong network characterised by cohesive and dense integration was negatively correlated with athlete burnout; and (4) the strong social network played a significant mediating role between perceived social support and athlete burnout. These findings could contribute to insights into the mechanisms by which perceived social Support relates to burnout in elite athletes, and provide crucial practical guidance for protecting and promoting their mental health and well-being.